2010
DOI: 10.5059/yukigoseikyokaishi.68.1185
|View full text |Cite
|
Sign up to set email alerts
|

Development of P-Spiro Chiral Aminophosphonium Salts as a New Class of Versatile Organic Molecular Catalyst

Abstract: A series of P spiro chiral tetraaminophosphonium salts have been designed and synthesized as a new class of organic molecular catalysts, and their inherent abilities to exert four different, synthetically relevant asymmetric catalyses have been brought out through the unique molecular design on a single core structure, N 4 P . Further, these catalyses have been applied to the development of various C C, C P, and C N bond forming reactions, in which the remarkably high catalytic performances and stereocontrolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Much to our surprise, our data clearly showed that the C(a) À H protons of 2 a BPh 4 À do not experience any significant ring current effect in CD 2 Cl 2 solution. Considering the relevance of phosphonium ion/anion interactions in crystal engineering, [21] anion recognition, [22] saltbased solvent systems, [23,24] photochemistry, [19,20,25] structure determination, [10,26] and organic synthesis, [27,28] we decided to carry out a more detailed investigation of the ion pairing in 2 a X À and related phosphonium salts.…”
Section: Introductionmentioning
confidence: 99%
“…Much to our surprise, our data clearly showed that the C(a) À H protons of 2 a BPh 4 À do not experience any significant ring current effect in CD 2 Cl 2 solution. Considering the relevance of phosphonium ion/anion interactions in crystal engineering, [21] anion recognition, [22] saltbased solvent systems, [23,24] photochemistry, [19,20,25] structure determination, [10,26] and organic synthesis, [27,28] we decided to carry out a more detailed investigation of the ion pairing in 2 a X À and related phosphonium salts.…”
Section: Introductionmentioning
confidence: 99%
“…37 Mannich reactions have been catalyzed by cyclopropenimine 69 and iminophosphorane bases. 70 Recently, Terada et al designed a superbasic organocatalyst consisting of a phosphazene and a chiral guanidine unit. 71 The cooperative effect of these two units leads to unprecedented enantioselectivity in the direct aza-Mannich reaction of less acidic pronucleophiles, such as αphenylthioacetate.…”
Section: Carbon-centered Superbasesmentioning
confidence: 99%
“…71 The cooperative effect of these two units leads to unprecedented enantioselectivity in the direct aza-Mannich reaction of less acidic pronucleophiles, such as αphenylthioacetate. Uraguchi and Ooi 70 73 for the preparation of chiral derivatizing agents 74 and in Strecker reactions at very low catalyst loading (0.1 mol %). 75 A growing field for superbase applications is also ring-opening polymerization processes.…”
Section: Carbon-centered Superbasesmentioning
confidence: 99%
“…The most prevalent superbase incorporated into organocatalysts is guanidines . In 1999, Corey described the use of a chiral C 2 -symmetric guanidine catalyst for the enantioselective Strecker reaction, and later Tan reported that a t Bu-substituted variant was effective in the enantioselective sulfa-Michael addition of aryl thiols to activated α-phthalimido acrylate esters. , Ishikawa, and more recently Terada, have shown important applications of other chiral guanidine constructs. , Ooi, and subsequently Terada also reported chiral P 1 phosphazene catalyst systems for activation and enantioselective reactions of challenging ketone substrates. , Lambert and Bandar described the application of chiral cyclopropenimine-containing catalysts as the superbase for enantioselective Michael and Mannich reactions of glycine-derived pronucleophiles . These catalyst systems constitute the state-of-the-art in chiral superbase chemistry (Figure C).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Ooi, and subsequently Terada also reported chiral P 1 phosphazene catalyst systems for activation and enantioselective reactions of challenging ketone substrates. 29,30 Lambert and Bandar described the application of chiral cyclopropenimine-containing catalysts as the superbase for enantioselective Michael and Mannich reactions of glycine-derived pronucleophiles. 31 These catalyst systems constitute the state-of-the-art in chiral superbase chemistry (Figure 1C).…”
Section: ■ Introductionmentioning
confidence: 99%